ANALISIS PENGARUH TINGKAT PENGETAHUAN FINTECH PEER TO PEER (P2P) LENDING SYARIAH TERHADAP PREFERENSI MAHASISWA (Studi Kasus Mahasiswa Perbankan Syariah UIN SMDD Bukittinggi Angkatan 2020) - Ardina Khairunnisa; Cahya Agung Mulyana (ADISAM PUBLISHER, 2024)
This research aims to analyze the influence of students' knowledge of Sharia Peer-to-Peer (P2P) lending fintech on their preferences in choosing financial services. The research adopts a quantitative approach using a survey conducted on the 2020 class of Sharia Banking students at UIN SMDD Bukittinggi. Data was collected through a questionnaire distributed to 79 respondents. The results show that the students' knowledge of Sharia P2P lending significantly affects their preference for selecting Sharia financial services. The study concludes that increasing financial literacy and knowledge of Sharia financial products is essential to encourage students' preferences towards Sharia-based financial services. The implications of these findings can be used to develop more effective educational programs to improve Sharia fintech literacy